On writing Soviet History of Central Asia: frameworks, challenges, prospects. Issue 4 (2nd October 2021) - Kassymbekova, Botakoz; Chokobaeva, Aminat
ABSTRACT: The article reviews major frameworks for re-evaluating Soviet Central Asian history in anglophone scholarship after the collapse of the Soviet Union. It tackles recent popular concepts such as 'modernity', 'development' and 'modernization' for analysing the Soviet past in the region. It questions the analytical value of the terms as well as their ability to capture the complexity of social, political and economic changes that Central Asia underwent in the course of seven decades between the October Revolution and the dissolution of the USSR. The article furthermore provides an overview of novel themes and approaches in the field and suggests themes for further research.